ANALISIS KETERAMPILAN METAKOGNISI SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA DI KELAS XI SMK NEGERI 1 SOSORGADONG - Darpin Sihotang; Tamin Ritonga; Roslian Lubis (JURNAL MathEdu (Mathematic Education Journal), 2021)
This study aims to describe students’ metacognition skill in completing mathematics’ questions at the eleventh grade students of SMK Negeri 1 Sosorgodang. This research conducted by applying quantitative descriptive method with 27 students as the sample and they were taken by using cluster random sampling technique from 95 students. Instrument of the research used test. The result of research shows 1) students who have high mathematic ability have very good metacognition, 2) students who have average mathematic ability have good metacognition, and 3) students who have low mathematic ability have less metacognition.